2020
DOI: 10.1051/0004-6361/202037964
|View full text |Cite
|
Sign up to set email alerts
|

A new study of the spectroscopic binary 7 Vul with a Be star primary

Abstract: We confirmed the binary nature of the Be star 7 Vul, derived a more accurate spectroscopic orbit with an orbital period of 69.d4212±0.d0034, and improved the knowledge of the basic physical elements of the system. Analyzing available photometry and the strength of the Hα emission, we also document the long-term spectral variations of the Be primary. In addition, we confirmed rapid light change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
3
13
1
Order By: Relevance
“…Therefore, the star rotates near its break‐up velocity, and the minimum possible inclination of the stellar rotation axis is i = 56° (respectively as low as i = 34° considering the 1 σ uncertainty of v crit ). The obtained value of v sin( i ) is in good agreement with those obtained by others earlier, for example, 420 ± 8 km s −1 by Harmanec (), ∼415 km s −1 by Walker (), or 400 ± 20 km s −1 by Reid et al (), while it deviates at the 2 σ level from the v sin( i ) values reported by Cazorla et al () (378 ± 15 km s −1 ), van Belle () (∼385 km s −1 ), and Howarth et al () (372 ± 30 km s −1 ). Zorec et al () and Simón‐Díaz & Herrero () obtained even smaller values of 344 ± 34 and ∼319 km s −1 , respectively.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the star rotates near its break‐up velocity, and the minimum possible inclination of the stellar rotation axis is i = 56° (respectively as low as i = 34° considering the 1 σ uncertainty of v crit ). The obtained value of v sin( i ) is in good agreement with those obtained by others earlier, for example, 420 ± 8 km s −1 by Harmanec (), ∼415 km s −1 by Walker (), or 400 ± 20 km s −1 by Reid et al (), while it deviates at the 2 σ level from the v sin( i ) values reported by Cazorla et al () (378 ± 15 km s −1 ), van Belle () (∼385 km s −1 ), and Howarth et al () (372 ± 30 km s −1 ). Zorec et al () and Simón‐Díaz & Herrero () obtained even smaller values of 344 ± 34 and ∼319 km s −1 , respectively.…”
Section: Resultssupporting
confidence: 91%
“…Similar conclusions were obtained by Vieira et al (2017). A correlation between Hα emission and visual magnitude strength has been proposed by Harmanec (1983) and more recently supported by Sigut & Patel (2013), who interpreted the correlation in terms of disks that grow in size and/or density with time. The Be star outbursts are presently being modeled within the theory of viscous decretion disks controlled by variable mass loss Ṁ and parameterized through the viscosity parameter α (Haubois et al 2012;Rímulo et al 2015).…”
Section: Introductionsupporting
confidence: 82%
“…Such binaries (with yet unseen companions) may also be found among the mid/late type B stars (e.g. 7 Vul, B5Ve, Harmanec et al 2020). These and similar systems with known orbital periods are included in the target list, where Polstar observations can be scheduled to cover the orbital phases.…”
Section: The Known Be+sdo Populationmentioning
confidence: 99%